Longman preparation series for the new TOEIC test. Advanced course - Lougheed, Lin (Pearson Education, 2007)
Longman Preparation Series for the New TOEIC® Test: Advanced Course, Fourth Edition, gives students the skills, strategy, practice, and confidence they need to increase their scores on the new TOEIC® test. Ideal for a TOEIC® test preparation course or for self-study, the Advanced Course is intended for students who achieve TOEIC® test scores from 450 to 850.